„f“ AND „h“ LETTERS' PROBLEM IN LATGALIAN LANGUAGE - Bierzeņš, Aņss Ataols (Via Latgalica, 2010)
In the article is told about the problem of letters’ (and sounds’) f and h in Latgalian language. These sounds have never been in any Latgalian dialect, in foreign words speakers always have been replaced them with other sounds. At the same time letters f and h have been used in written Latgalian at all times: from the first known book „Evangelia toto anno“ to the present day. What to do in this situation: to keep the way of the still alive traditional spoken language, or to yield to the pressure of other languages?The author analyzes a variety of sources: tells about reconstructions of source languages and opinions of their researchers about presence/absence of these sounds in them, deals with f in contemporary Eurasian languages (Eastern Slavic: Russian, Ukrainian, Belarusian; Finnic: Finnish, Estonian, Vyru; Turkic: Kyrgyz, Kazakh, Chuvash, Yakut; Persian: Pashto; Baltic: Lithuanian, Samogitian) and h in contemporary Eurasian languages (French, Kazakh, Lithuanian, Samogitian). Latgalian and Latvian dialects’ recordings, folk songs, ancient texts (from XVI–XVIII centuries), as well as Latgalian contemporary literature are analyzed. The author also evaluates inclusion of letters f and h in alphabet of the official Latgalian terms of spelling in year 2007.Author establishes that there are five possible paths:1) to use the f and h in all the words where they are in Latvian, Russian or other languages;2) to keep p, k, g and c in traditionally used words, but to put f and h in newly borrowed ones;3) do not use the f and h at all;4) to use both variants parallely in the same words;5) to write f and h, but to pronounce them as p and k.Author concludes that the actualy usable are only two of them: the second one – the way of a compromise, and the third one – as the most appropriate to Latgalian phonological system.